2017
DOI: 10.1007/s11060-017-2699-y
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative language ability in patients with presumed low-grade glioma

Abstract: In patients with low-grade glioma (LGG), language deficits are usually only found and investigated after surgery. Deficits may be present before surgery but to date, studies have yielded varying results regarding the extent of this problem and in what language domains deficits may occur. This study therefore aims to explore the language ability of patients who have recently received a presumptive diagnosis of low-grade glioma, and also to see whether they reported any changes in their language ability before r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…These studies have traditionally proposed patients' age and tumor location as the most significant variables for postsurgical prognosis (Armstrong et al, 2003;Habets et al, 2014;Klein et al, 2001). For instance, Kaleita et al (Kaleita et al, 2004) Previous studies have considered language impairments to be the ones most impacting on patients' quality of life and have included them as the primary outcome to be predicted in the studies (Antonsson et al, 2018;Duffau, Gatignol, Mandonnet, Capelle, & Taillandier, 2008;Kim et al, 2009). Our results highlighted the importance of the inferior and superior longitudinal fasciculi, relevant for language production and comprehension, when introducing connectivity variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have traditionally proposed patients' age and tumor location as the most significant variables for postsurgical prognosis (Armstrong et al, 2003;Habets et al, 2014;Klein et al, 2001). For instance, Kaleita et al (Kaleita et al, 2004) Previous studies have considered language impairments to be the ones most impacting on patients' quality of life and have included them as the primary outcome to be predicted in the studies (Antonsson et al, 2018;Duffau, Gatignol, Mandonnet, Capelle, & Taillandier, 2008;Kim et al, 2009). Our results highlighted the importance of the inferior and superior longitudinal fasciculi, relevant for language production and comprehension, when introducing connectivity variables.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have considered language impairments to be the ones most impacting on patients’ quality of life and have included them as the primary outcome to be predicted in the studies (Antonsson et al, 2018; Duffau, Gatignol, Mandonnet, Capelle, & Taillandier, 2008; Kim et al, 2009). Our results highlighted the importance of the inferior and superior longitudinal fasciculi, relevant for language production and comprehension, when introducing connectivity variables.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a brain tumor around the language network can disrupt the assessment of language dominance with fMRI [13,26,27]. Based on prior research [1,12,28,29], it is suggested that fMRI estimates of language dominance can be distorted (usually decreased) by two subcategories of tumor-related confounds: (a) tumor characteristics [1,12,28,29], and (b) tumor-induced conditions [30][31][32]. These two subcategories are presented in Table 2.…”
Section: Organization Of Variables Affecting Fmri Estimates Of Language Dominance In Patients With Brain Tumors 21 Confounding Vs Modulatmentioning
confidence: 99%
“…(a) Aphasia-disrupted language comprehension and/or production has been reported in between 10.4 to 36.4% of individuals with brain tumors residing in the languagedominant left hemisphere [30,[52][53][54][55]. The vast discrepancies in aphasia reports may result from methodological differences in patient selection and assessments between studies, such as including patients with both low and high tumor grades or enrolling patients with recurring tumors [30]. In general, patients with low-grade gliomas have milder or no language impairments compared to high-grade gliomas.…”
Section: Tumor-induced Conditionsmentioning
confidence: 99%
See 1 more Smart Citation